IMPACT OF SYMPTOM BURDEN AND HEALTH-RELATED QUALITY OF LIFE (HRQOL) ON ESOPHAGEAL MOTOR DIAGNOSES - Reddy, Chanakyaram A. (Neurogastroenterol Motil, 2016)
High resolution manometry (HRM) categorizes esophageal motor processes into specific Chicago Classification (CC) diagnoses, but the clinical impact of these motor diagnoses on symptom burden remain unclear. METHODS: 211 subjects (56.8±1.0 yrs, 66.8% F) completed symptom questionnaires [GERDQ, Mayo dysphagia questionnaire (MDQ), visceral sensitivity index (VSI), short-form 36 (SF-36), dominant symptom index (DSI), and global symptom severity (GSS) on a 100-mm visual analog scale] prior to HRM. Subjects were stratified according to CC v3.0 and by dominant presenting symptom; contraction wave abnormalities (CWA) were evaluated within ‘normal’ CC. Symptom burden, impact of diagnoses, and HRQOL were compared within and between cohorts. RESULTS: Major motor disorders had highest global symptom burden (p=0.02), ‘normal’ had lowest (p<0.01). Dysphagia (MDQ) was highest with esophageal outflow obstruction (p=0.02), but reflux symptoms (GERDQ) were similar in CC cohorts (p=ns). Absent contractility aligned best with minor motor disorders. Consequently, pathophysiologic categorization into outflow obstruction, hypermotility, and hypomotility resulted in a gradient of decreasing dysphagia and increasing reflux burden (p<0.05 across groups); GSS (p=0.05) was highest with hypomotility and lowest with ‘normal’ (p=0.002). Within the ‘normal’ cohort, 33.3% had CWA; this subgroup had symptom burden similar to hypermotility. Upon stratification by symptoms, symptom burden (GSS, MDQ, HRQOL) was most profound with dysphagia. CONCLUSIONS: CC v3.0 diagnoses identify subjects with highest symptom burden, but pathophysiologic categorization may allow better stratification by symptom type and burden. CWA are clinically relevant and different from true normal motor function. Transit symptoms have highest yield for a motor diagnosis.